Analysis of the Resilience of Balance of Payments Using Comprehensive Evaluation - Shixin Fan; Ying Liu (Journal of Mathematics)
Globalization has brought increased attention to the balance of payments situation from a variety of countries. The traditional method of measuring balance of payments may not be applicable in certain situations. This paper draws on the idea of economic resilience, uses the transmission mechanism of balance of payments imbalance, and establishes a system of balance of payments imbalance resilience to provide a complement to the traditional measure. In this article, we establish a system of balance of payments resilience and ensure its reasonableness and effectiveness. The main conclusions are as follows: (1) balance of payments resilience score can be used as a reference and early warning indicator of a country’s balance of payments situation and improves the measurement of balance of payments. (2) Improving the country’s unemployment rate and boosting adjusted net savings will significantly upgrade the balance of payments situation. Improving foreign capital adequacy and foreign exchange market conditions is more beneficial for improving the country’s rank of resilience score.